Pengembangan Media Pembelajaran Menggunakan Software Articulate Storyline pada Pembelajaran Dasar Listrik Elektronika - Khairiman Iman Syabri; Elfizon Elfizon (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2020)
This research is a process carried out in developing a learning media in Basic Electricity and Electronics subjects using articulate storyline software at State Vocational High School 2 Lubuk Basung. The resulting media is in the form of interactive media, so that media can be used must go through a series of assessment processes. The purpose of this research is to produce learning media that are categorized as valid and practical. This research is based on problems related to learning media used in Basic Electrical and Electronics subjects that have not provided optimal results on student learning outcomes and low interest and student motivation in the learning process. The availability of learning media that is less varied and the tendency of teachers to use the same media causes saturation of students. Media development is carried out using the Research and Development (R & D) research method using the 4-D (four D) development model through four main procedures, namely definition, design, development, and dissemination. The results obtained in research with the feasibility of media by material experts on the content aspect were valid and the learning aspect was valid. The feasibility of media by media experts on technical aspects is valid and functional aspects are categorized as valid. The practicality assessment of the media resulted in very practical categories.